Intracochlear schwannoma: about a case - Mercado Martinez, Victor; Torres Moyano, Francisco; Pino Urrutia, Carlos; Fuentealba Bassaletti, Constanza; Krishnan Muthaiah, Vijaya Prakash; Novoa Cornejo, Ignacio (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Vestibular schwannoma is a benign tumor that originates from Schwann cells. It is most often found in the internal auditory meatus or cerebellopontine angle. Less frequently, intralabyrinthine localization (IL) can be found. These benign lesions usually present with progressive sensorineural hearing loss, tinnitus, and vertigo. Magnetic resonance imaging (MRI) allows a precise diagnosis of these tumors, also defining their exact location within the labyrinth. Currently, the treatment of IL may require radiosurgery, tumor removal surgery, and tumor follow-up with MRI. We will present a clinical case of a patient with intracochlear schwannoma (ICS) of the left ear.